On some species of Apatetica Westwood (Coleoptera: Staphylinidae: Apateticinae) - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2018)
Eight species of Apatetica Westwood, 1848 are (re-)described and illustrated, six of them for the first time: Apatetica viridipennis Fauvel, 1895 (North India); A. glaucipennis spec. nov. (Nepal); A. confusa spec. nov. (Myanmar; previously confounded with A. viridipennis); A. aspera spec. nov. (China: Sichuan); A. laevicollis Fauvel, 1904 (Vietnam); A. glabra spec. nov. (China: Yunnan); A. gibba spec. nov. (China: Gansu); A. curtipennis spec. nov. (China: Yunnan). A lectotype is designated for Apatetica laevicollis. The first confirmed record of A. laevicollis since the original description is reported. The genus currently includes 25 described species distributed in the southern East Palaearctic and Oriental regions.